Testosterone induces plumage ornamentation followed by enhanced territoriality in a female songbird. (26th August 2020) - Boersma, Jordan; Enbody, Erik D; Jones, John Anthony; Nason, Doka; Lopez-Contreras, Elisa; Karubian, Jordan; Schwabl, Hubert
Abstract: We know little of the proximate mechanisms underlying the expression of signaling traits in female vertebrates. Across males, the expression of sexual and competitive traits, including ornamentation and aggressive behavior, is often mediated by testosterone. In the white-shouldered fairywren ( Malurus alboscapulatus ) of New Guinea, females of different subspecies differ in the presence or absence of white shoulder patches and melanic plumage, whereas males are uniformly ornamented. Previous work has shown that ornamented females circulate more testosterone and exhibit more territorial aggression than do unornamented females. We investigated the degree to which testosterone regulates the expression of ornamental plumage and territorial behavior by implanting free-living unornamented females with testosterone. Every testosterone-treated female produced a male-like cloacal protuberance, and 15 of 20 replaced experimentally plucked brown with white shoulder patch feathers but did not typically produce melanic plumage characteristic of ornamented females. Testosterone treatment did not elevate territorial behavior prior to the production of the plumage ornament or during the active life of the implant. However, females with experimentally induced ornamentation, but exhausted implants, increased the vocal components of territory defense relative to the pretreatment period and also to testosterone-implanted females that did not produce ornamentation. Our results suggest that testosterone induces partial acquisition of the ornamental female plumage phenotype and that ornament expression, rather than testosterone alone, results in elevations of some territorial behaviors. Abstract : Testosterone regulates the expression of a suite of competitive traits in male organisms and could have a similar function in females. Empirical tests are needed to determine the extent to which testosterone promotes the production of ornamentation and competitive behaviors in female animals. We supplemented testosterone in unornamented females of a species where naturally occurring ornamented females circulate higher testosterone and are more territorially aggressive. Implanted females produced partial ornamentation and this ornament expression, rather than testosterone circulation per se, appears to be associated with increased territoriality in treatment females.